The emergence of modern architecture - Lefaivre, Liane. 4 0 16; Tzonis, Alexander; 5 (London ;;New York : Routledge, 2004)
Contains 140 documents that combine to provide a history of architecture in the years between 1000 and the first decade of the nineteenth century.
Includes bibliographical references (p. 502-525) and indexes.
Adult;Adult.
Keywords: 2 -- 0; 6; History.;History. -- Architecture;Architecture;Architecture;Architecture -- Sources.;Sources.; 20; 2